Method for producing electrochemiluminescent nanoprobe, electrochemiluminescent nanoprobe, electrochemiluminescent sensor, method for detecting electrochemiluminescence, and kit for detecting electrochemiluminescence
By employing hot exciton nanoparticles modified with oligonucleotide-quencher molecules, the method addresses the inefficiencies in ECL detection, providing a sensitive and wide-range detection solution for target molecules.
Patent Information
- Application Number
- JP2024090811
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-06-09
- Filing Date
- 2024-06-04
- Publication Date
- 2024-12-19
AI Technical Summary
Existing electrochemiluminescence (ECL) technologies face limitations in achieving high exciton utilization rate and radiative transition rate simultaneously, leading to suboptimal luminous efficiency and intensity, particularly in the context of electrochemiluminescence detection methods.
The production of electrochemiluminescent nanoprobes using hot exciton organic light-emitting molecules, synthesized through polymerization with copolymer molecules and modified with oligonucleotide chains containing quencher molecules, to create nanoparticles that enhance detection sensitivity and range.
The method achieves a wide detection range and extremely high sensitivity for target molecules, enabling rapid, non-amplified, high-throughput detection through the use of electrochemiluminescent sensors and detection kits.
Smart Images

Figure 2024177109000001_ABST
Abstract
Description
[Technical field]
[0001] SUMMARY OF THE PRESENT EMBODIMENTS The present invention relates to a method for producing an electrochemiluminescent nanoprobe, an electrochemiluminescent nanoprobe, an electrochemiluminescent sensor, an electrochemiluminescent detection method, and a kit for electrochemiluminescence detection. [Background technology]
[0002] Electroluminescence (EL) is the phenomenon in which a light-emitting material emits light when excited by a current and voltage through an electric field, and is the process of directly converting electrical energy into light energy. Organic electroluminescence is the phenomenon in which a thin-film element made of an organic light-emitting material emits light when excited by an electric field. The principle of light emission in an organic electroluminescence element is that, when driven by an external voltage, electrons and holes injected from an electrode combine in the organic material to release energy, which is then transferred to the molecules of the organic light-emitting material, exciting them and causing them to transition from the ground state to an excited state. When the excited molecules return from the excited state to the ground state, they undergo radiative transition, causing light emission. The excited state can be divided into singlet (S) excitons and triplet (T) excitons, depending on the difference in spin multiplicity. Molecules in the excited state are in the lowest energy singlet excited state S. 1 or triplet excited state T 1 or a higher singlet excited state (S 2 , S 3 , S 4 , …) or triplet excited state (T 2 , T 3 , T 4 , ...). 1 When a molecule in an excited state undergoes a radiative transition, it becomes S 0 When it returns to the ground state, it emits "fluorescence." T 1 When a molecule in an excited state undergoes a radiative transition, it becomes S 0 When it returns to the ground state, it generates "phosphorescence emission" (see FIG. 19). FIG. 19 is a schematic diagram showing the emission principle of hot exciton materials with hybrid local-charge transfer excited state (HLCT) properties.
[0003] Electrochemiluminescence (ECL) technology is a method that uses electrochemical principles to generate an excited state on the surface of an electrode, resulting in specific light emission. The excited state in the electrochemiluminescence process is generated by an electron transfer reaction between an intermediate radical formed by electron transfer between an electroactive material and an electrode.
[0004] Depending on the luminescent reagent, electrochemiluminescence systems can be divided into metal complex electrochemiluminescence systems and organic compound electrochemiluminescence systems (hereinafter sometimes referred to as "organic luminescent materials"), such as aromatic hydrocarbons such as organic fluorenes, BODIPY derivatives, fluorene-based polymers, and various organic nanomaterials. Common electrochemiluminescent metal complexes include, for example, tris(bipyridine)ruthenium(II) complex ions (Ru(bpy) 3 2+ ), which belongs to the phosphorescence emission system. When it is used as an ECL emission probe, the exciton utilization rate can reach 100%, so tris(bipyridine)ruthenium(II) complex ion (Ru(bpy) 3 2+ The electrochemiluminescence detection method based on ) has become the standard method for electrochemiluminescence detection. Meanwhile, the above organic light-emitting materials belong to the fluorescent light-emitting system, and the exciton utilization rate can only reach 25%.
[0005] In the excited state, the organic light-emitting materials currently used in the field of electrochemiluminescence mainly have two traditional excited state modes, namely, locally excited state (LE) and charge-transfer excited state (CT). Due to the electron-hole distribution of these two excited states and the binding energy characteristics of the excitons formed, the exciton utilization rate of the locally excited state is low, resulting in a high radiative transition rate / quantum yield (Φ PL ) is high, and the exciton utilization rate of the charge-transfer excited state is high, resulting in a low radiative transition rate / quantum yield, and the two cannot simultaneously achieve high exciton utilization rate and high radiative transition rate / quantum yield, resulting in the luminescence efficiency and intensity not reaching the ideal optimum level, which limits the efficiency of downstream applications, such as electrochemiluminescence.
[0006] In 2012, Ma Oguang, Yang Bing and others innovatively applied the photophysical phenomenon of reverse intersystem crossing (RISC) to the design of organic electroluminescent materials and successfully developed a series of donor-acceptor fluorescent materials with different light colors. The effective high-level reverse intersystem crossing process greatly improved the exciton utilization rate of the electroluminescent device. Here, the high-level triplet state (T n , n ≥ 2) and singlet states (S m , m ≧ 1) is called the hot exciton process, the light-emitting mechanism realized based on the hot exciton process is called the hot exciton mechanism, and the light-emitting material with obvious hot exciton reverse intersystem crossing is called the hot exciton material. Hot exciton materials generally have a large T n -T 1 Energy levels and small T n -S m state energy level. Large T n -T 1 Energy level is T n From T 1 The internal conversion to β- n -S m Energy level is T n From S m The reverse intersystem crossing rate to T n From S m Intersystem crossing to T n From T 1 Since the internal conversions to singlet S and triplet S compete with each other, theoretically, the reverse intersystem crossing rate can be high enough to completely suppress the internal conversion and convert all high-ranking triplet excitons into singlet excitons, so that the exciton utilization rate of the hot exciton material can reach 100% (see Non-Patent Document 1, Figure 19). This allows the hot exciton material to realize reverse intersystem crossing (hRISC) through an independent "hot exciton" channel to produce singlet S. 1 It is possible to increase the rate of exciton generation. At the same time, S 1The hot exciton material has hybrid locally-excited and charge-transfer (HLCT) properties, and can simultaneously have high exciton utilization and high quantum yield, because the hot exciton has the high exciton utilization rate of the CT state and the high radiative emission property of the LE state. The hybrid locally-excited and charge-transfer excited state not only contains the properties of the locally excited state (LE), but also the charge-transfer (CT) excited state properties, but is not a simple mixture between the locally excited state and the charge-transfer excited state, but a single excited state formed after hybridization.
[0007] At present, hot exciton materials are mainly used in the field of semiconductor materials, such as in the field of organic electroluminescence diodes (OLEDs) (see Non-Patent Document 2), which are new luminescent materials following the first generation organic luminescent materials (fluorescent materials), second generation organic luminescent materials (phosphorescent materials), and third generation organic luminescent materials (thermally activated delayed fluorescence, TADF) materials.
[0008] The excellent optical properties of hot exciton materials make them attractive for use in biological detection. Patent Document 1 attempts to use hot exciton materials in fluorescence detection, but there are currently no successful examples in the field of ECL detection. [Prior art documents] [Patent documents]
[0009] [Patent Document 1] China Patent Application Publication No. 110981821 [Non-patent literature]
[0010] [Non-Patent Document 1] Xu Yuwei, "Research on the High-Level Reverse Intersystem Crossing Process and Photoelectric Performance of Hot Exciton Luminescent Materials", Doctoral Dissertation, South China University of Technology, 2020 [Non-Patent Document 2] Xiaojie Chen, Dongyu Ma et al., “Hybridized Local and Charge-Transfer Excited-State Fluorophores through the Regulation of the Donor-Acceptor Torsional Angle For Highly Efficient Organic Light-Emitting Diodes”, CCS Chem. 2022, 4, 1284-1294 Summary of the Invention [Problem to be solved by the invention]
[0011] The problem to be solved by the present invention is to provide a method for producing an electrochemiluminescent nanoprobe having a wide detection range and high sensitivity, an electrochemiluminescent nanoprobe, an electrochemiluminescent sensor, an electrochemiluminescent detection method, and an electrochemiluminescence detection kit. [Means for solving the problem]
[0012] The manufacturing method of the electrochemiluminescent nanoprobe of the embodiment includes a hot exciton nanoparticle synthesis step of polymerizing hot exciton organic luminescent molecules and copolymer molecules to synthesize hot exciton nanoparticles, and a hot exciton nanoparticle modification step of modifying the obtained hot exciton nanoparticles with an oligonucleotide chain having a quencher molecule modification to obtain modified hot exciton nanoparticles. [Brief description of the drawings]
[0013] [Figure 1] FIG. 1 is a schematic diagram showing a method for producing an electrochemiluminescent nanoprobe of the present invention. [Diagram 2] FIG. 2 is a schematic diagram of an ECL switch based on the ssDNA-BB NRs nanoprobe of the present invention. [Diagram 3] FIG. 3 is a schematic diagram of the fabrication and detection of a sensor array based on the ssDNA-BB NRs of the present invention. [Figure 4]FIG. 4 is a schematic diagram contrasting the light emission principles of TADF compounds and hot exciton materials. [Figure 5A] FIG. 5A is a diagram showing the results of nuclear magnetic ( 1 H NMR) and mass spectrometry of the BCzP-BT molecule prepared in Example 1 of the present invention. [Figure 5B] FIG. 5B is a diagram showing the results of nuclear magnetic ( 1 H NMR) and mass spectrometry of the BCzP-BT molecule prepared in Example 1 of the present invention. [Figure 6A] FIG. 6A is a diagram showing the analysis results of the excited state of the BCzP-BT molecule prepared in Example 1 of the present invention. [Figure 6B] FIG. 6B is a diagram showing the analysis results of the excited state of the BCzP-BT molecule prepared in Example 1 of the present invention. [Figure 7A] FIG. 7A is a diagram showing the excited state properties of the BCzP-BT molecule prepared in Example 1 of the present invention. [Figure 7B] FIG. 7B is a diagram showing the excited state properties of the BCzP-BT molecule prepared in Example 1 of the present invention. [Figure 8A] FIG. 8A is a diagram showing the analysis results of the possibility of hot exciton processes of BCzP-BT prepared in Example 1 of the present invention. [Figure 8B] FIG. 8B is a diagram showing the analysis results of the possibility of hot exciton processes of BCzP-BT prepared in Example 1 of the present invention. [Figure 9A] FIG. 9A is a diagram showing the analysis results of the characteristics of the BB NRs produced in Example 1 of the present invention. [Figure 9B] FIG. 9B is a diagram showing the analysis results of the characteristics of the BB NRs produced in Example 1 of the present invention. [Figure 9C] FIG. 9C is a diagram showing the analysis results of the characteristics of the BB NRs produced in Example 1 of the present invention. [Figure 9D] FIG. 9D is a diagram showing the analysis results of the characteristics of the BB NRs produced in Example 1 of the present invention. [Figure 9E] FIG. 9E is a diagram showing the analysis results of the characteristics of the BB NRs produced in Example 1 of the present invention. [Figure 10A] FIG. 10A shows the analysis results of the ECL properties of the BB NRs prepared in Example 1 of the present invention. [Figure 10B] FIG. 10B shows the analysis results of the ECL properties of the BB NRs prepared in Example 1 of the present invention. [Figure 11A] FIG. 11A shows the ECL analysis results of the BB NRs prepared in Example 1 of the present invention in the presence of a co-reactant. [Figure 11B] FIG. 11B shows the ECL analysis results of the BB NRs prepared in Example 1 of the present invention in the presence of a co-reactant. [Figure 11C] FIG. 11C shows the ECL analysis results of the BB NRs prepared in Example 1 of the present invention in the presence of a co-reactant. [Figure 11D] FIG. 11D shows the ECL analysis results of the BB NRs prepared in Example 1 of the present invention in the presence of a co-reactant. [Figure 11E] FIG. 11E shows the ECL analysis results of the BB NRs prepared in Example 1 of the present invention in the presence of a co-reactant. [Figure 11F] FIG. 11F shows the ECL analysis results of the BB NRs prepared in Example 1 of the present invention in the presence of a co-reactant. [Figure 12A] FIG. 12A shows the ECL efficiency of the BB NRs prepared in Example 1 of the present invention based on Ru(bpy)3 2+. [Figure 12B] FIG. 12B shows the ECL efficiency of the BB NRs prepared in Example 1 of the present invention based on Ru(bpy)3 2+. [Figure 12C] FIG. 12C shows the ECL efficiency of the BB NRs prepared in Example 1 of the present invention based on Ru(bpy)3 2+. [Figure 12D] FIG. 12D shows the ECL efficiency of the BB NRs prepared in Example 1 of the present invention relative to Ru(bpy)3 2+. [Figure 13A] FIG. 13A shows the analysis results of ECL assignment of BB NRs prepared in Example 1 of the present invention. [Figure 13B]FIG. 13B shows the analysis results of ECL assignment of the BB NRs prepared in Example 1 of the present invention. [Figure 13C] FIG. 13C shows the analysis results of ECL assignment of BB NRs prepared in Example 1 of the present invention. [Figure 14A] FIG. 14A shows the analysis results of the characteristics of the ssDNA-BB NRs probe produced in Example 2 of the present invention. [Figure 14B] FIG. 14B shows the analysis results of the characteristics of the ssDNA-BB NRs probe produced in Example 2 of the present invention. [Figure 14C] FIG. 14C shows the analysis results of the characteristics of the ssDNA-BB NRs probe produced in Example 2 of the present invention. [Figure 15A] FIG. 15A shows the results of an analysis of the feasibility of the ssDNA-BB NRs probe signal switch prepared in Example 2 of the present invention. [Figure 15B] FIG. 15B shows the results of feasibility analysis of the ssDNA-BB NRs probe signal switch prepared in Example 2 of the present invention. [Figure 16A] FIG. 16A shows the detection results of ECL detection performed under different detection conditions in Example 3 of the present invention. [Figure 16B] FIG. 16B is a diagram showing the detection results of ECL detection performed under different detection conditions in Example 3 of the present invention. [Figure 16C] FIG. 16C shows the detection results of ECL detection performed under different detection conditions in Example 3 of the present invention. [Figure 17A] FIG. 17A is a diagram showing the results of ECL imaging when the ITO electrode and Au / ITO of Example 3 of the present invention are used. [Figure 17B] FIG. 17B is a diagram showing the results of ECL imaging when the ITO electrode and Au / ITO of Example 3 of the present invention are used. [Figure 17C] FIG. 17C is a diagram showing the results of ECL imaging when the ITO electrode and Au / ITO of Example 3 of the present invention are used. [Figure 18A]FIG. 18A shows the detection results of ECL detection of HPV16 DNA target nucleic acid using a sensor array in Example 3 of the present invention. [Figure 18B] FIG. 18B shows the detection results of ECL detection of HPV16 DNA target nucleic acid using a sensor array in Example 3 of the present invention. [Figure 19] FIG. 19 is a schematic diagram illustrating the luminescence principle of hot exciton materials with hybrid local-charge transfer excited state (HLCT) properties. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] As is well known, organic electroluminescence diodes (OLEDs) are all-solid-state devices and have no liquid components. In organic electroluminescence diodes, luminescent molecules are excited under the action of an external voltage to transition from the ground state to the excited state, and when the excited molecules return from the excited state to the ground state, they undergo radiative transition to generate light. On the other hand, the detection environment of electrochemiluminescence is liquid, and the luminescent molecules undergo an electrochemical reaction on the electrode surface to generate an excited state, and then undergo radiative transition to emit light. Therefore, the luminescence principles and luminescence environments of both organic electroluminescence diodes and electrochemiluminescence are different. When considering using hot exciton materials currently used in the field of organic electroluminescence diodes (OLEDs) as luminescent molecules for electrochemiluminescence (ECL) detection, there are firstly problems to be considered, such as feasibility and reliability.
[0015] As a result of extensive research into the above problems, the inventors of the present application have found that by using nanotechnology to produce electrochemiluminescent nanoprobes (hereinafter also referred to as "ECL nanoprobes") from hot exciton organic luminescent molecules and modifying them with oligonucleotide chains modified with quencher molecules, the overall efficacy of electrochemiluminescence can be improved, thereby realizing rapid, non-amplified, high-throughput detection of target molecules, with a wide detection range and extremely high sensitivity.
[0016] The present invention is the first to apply hot exciton organic luminescent molecules to the field of electrochemiluminescence, and the first to manufacture nanoparticles using the hot exciton organic luminescent molecules as luminescent bodies, thereby enabling rapid, non-amplified, high-throughput detection of target molecules to be realized, and providing an electrochemiluminescent (ECL) nanoprobe based on the hot exciton organic luminescent molecules having a wide detection range and extremely high sensitivity, as well as a sensor, detection method, and detection kit using the electrochemiluminescent nanoprobe.
[0017] Hereinafter, specific embodiments of the present invention will be described in detail. Note that the following description of the embodiments is only for the purpose of explaining the inventive concept of the present invention, and is not intended to limit the present invention.
[0018] <Electrochemiluminescent nanoprobe and its manufacturing method> One embodiment of the present invention relates to a method for producing an electrochemiluminescent nanoprobe, comprising: a hot exciton nanoparticle synthesis step of polymerizing hot exciton organic luminescent molecules and copolymer molecules to synthesize hot exciton nanoparticles; and a hot exciton nanoparticle modification step of modifying the obtained hot exciton nanoparticles with an oligonucleotide chain having a quencher molecule modification to obtain modified hot exciton nanoparticles.
[0019] (Hot exciton organic light-emitting molecules) The hot exciton organic light-emitting molecule used in the present invention is not particularly limited, and any hot exciton organic light-emitting molecule having the property of a hybrid local charge-transfer excited state can be used, for example, various hot exciton organic light-emitting molecules described in Non-Patent Documents 1 and 2.
[0020] Hot exciton materials are molecules that have the property of a hybrid locally-excited and charge-transfer (HLCT) excited state. Note that molecules that have a hybrid locally-excited and charge-transfer excited state are not necessarily hot exciton materials; for example, singlet and triplet materials have the property of a hybrid locally-excited and charge-transfer excited state, but do not belong to the hot exciton materials.
[0021] Hot exciton materials generally have one-dimensional fused ring structures as structural units and have donor cells that contain heteroatoms.
[0022] Examples of the condensed ring structure include a benzene ring, a naphthalene ring, and an anthracene ring, and the benzene ring, the naphthalene ring, and the anthracene ring may have a substituent. A specific structural structure of the donor-acceptor unit may be, for example, a DA type structure or a DAD type structure, etc. D represents a donor unit, and A represents an acceptor unit.
[0023] The donor-acceptor unit may be, for example, one composed of a donor (D) selected from group (a) of the following chemical formula (1) and an acceptor (A) selected from group (b) of the following chemical formula (2).
[0024] [ka]
[0025] [ka]
[0026] Hot exciton materials are a kind of luminescent materials which break through the spin-statistical limitations of traditional fluorescent materials. The types of emitted light include blue hot exciton materials, green hot exciton materials and red hot exciton materials.
[0027] Due to the suitable donor-acceptor strength of hot exciton materials, it is easier to obtain pure blue and deep blue light emission in the molecular design of DA-type fluorescent materials.Currently, blue hot exciton materials that have been successfully manufactured include blue hot exciton materials containing phenanthrene imidazole units, blue hot exciton materials containing anthracene units and other kinds of blue hot exciton materials.
[0028] Examples of blue light hot exciton materials containing phenanthrene imidazole units include blue light hot exciton materials containing phenanthrene imidazole units shown in the following chemical formulas (3) and (4).
[0029] [ka]
[0030] [ka]
[0031] An example of the anthracene unit-containing blue light hot exciton material is the blue light hot exciton material having an anthracene unit represented by the following chemical formula 5.
[0032] [ka]
[0033] Other kinds of blue light hot exciton materials include, for example, other kinds of blue light hot exciton materials shown in Chemical Formula 6 below.
[0034] [ka]
[0035] A representative green hot exciton material is, for example, the green hot exciton material shown in Chemical Formula 7 below.
[0036] [ka]
[0037] A representative red light hot exciton material is, for example, the red light hot exciton material shown in Chemical Formula 8 below.
[0038] [ka]
[0039] In addition, in the DAD-type hot exciton material, the connection between the acceptor (A) unit and the donor (D) unit may be ortho-position connection, meta-position connection, or para-position connection. Here, the para-position connection can reduce the spatial resistance, so that the twist angle between the acceptor (A) unit and the donor (D) unit is reduced, and a more locally excited component can be provided, resulting in faster radiation decay. This is more preferable because it can obtain a higher external quantum efficiency (EQE) than the ortho and meta positions. For example, in the examples of the present invention, 4,7-bis(4-(9H-carbazol-9-yl)phenyl)benzo[c][1,2,5]thiadiazole (p-BCzP-BT) is exemplified. In this compound, the electron donor (D) is carbazole, and the electron acceptor (A) is benzothiadiazole.
[0040] In addition, any hot exciton material having hybrid local charge transfer excited state (HLCT) properties can be used in the present invention. The hot exciton materials listed above are merely examples, and as will be clear to those skilled in the art, derivatives formed by substituting the above compounds with one or more substituents (e.g., alkyl groups, hydroxyl groups, halogens, etc.), and their spatial isomers, etc. can be used in the present invention in the same way.
[0041] The method for producing the hot exciton material used in the present invention is not particularly limited, and can be synthesized by chemical reaction through synthetic routes such as Suzuki coupling reaction, Scherrer coupling reaction and cross-coupling reaction, or can be purchased through commercial routes, and is not particularly limited.
[0042] In the examples of the present invention, the synthetic route of Suzuki coupling reaction is adopted, but other synthetic routes may be adopted as necessary. Suzuki coupling reaction is a commonly used carbon-carbon bond forming reaction in which aryl or alkenyl boronic acid is reacted with halogenated aromatic hydrocarbons such as chlorine, bromine, or iodine using zero-valent palladium as a catalyst. Palladium catalysts include, for example, tetrakis(triphenylphosphine)palladium (Pd(PPh 3 ) 4 ), Pd[P(o-toly) 3 ] 3 and Buchwald catalyst, etc. can be used. As the aryl or alkenyl boronic acid and the halogenated aromatic hydrocarbon, corresponding compound raw materials can be adopted according to the electron donor (D) and the electron acceptor (A) in the hot exciton organic light-emitting molecule to be synthesized as necessary, and are not particularly limited.
[0043] (Synthesis of hot exciton nanoparticles) In the present invention, hot exciton nanoparticles are synthesized by polymerizing hot exciton organic light-emitting molecules and copolymer molecules.
[0044] The nanoparticles in the present invention refer to particles in which at least one dimension in a three-dimensional space is nano-sized (0.1 to 100 nm). Specifically, the nanoparticles may be in various geometric forms such as nanoballs, nanotubes, nanorods, or nano-onions. By forming hot exciton organic luminescent molecules into a nano-shape, the ECL response signal can be effectively amplified, and the detection limit, detection range, selectivity, stability, etc. of the ECL sensor can be improved. In the present invention, as in the examples described below, materials in the form of nanorods (NR) were successfully prepared, but the nanoparticles that can be used in the present invention are not limited to nanorods, and other nano-shapes such as nanoballs can also be formed depending on the compound raw material and synthesis route adopted.
[0045] In the present invention, the hot exciton organic light-emitting molecules and the copolymer molecules can be synthesized by known methods for preparing organic material nanostructures in the prior art, including but not limited to nanocoprecipitation, microemulsion and self-assembly methods (Liu Ronghua, Preparation and Application of Novel Fluorescent Conjugated Polymer Nanoparticles, Beijing University of Science and Technology Doctoral Dissertation, 2018). Here, from the viewpoint of biocompatibility, it is more preferable to use the microemulsion and nanocoprecipitation methods.
[0046] In the microemulsion method, highly biocompatible and stable luminescent molecule nanoparticles can be obtained by coating luminescent molecules with non-toxic, non-immunogenic hydrophilic polymers, such as polyethylene glycol (PEG), polyethylene glycol-phosphatidylethanolamine (PEG-PE), and other polyethylene glycol molecules, and biopolymers, such as phospholipids.
[0047] In the nano-coprecipitation method, luminescent molecules are dissolved in a good solvent, and then a large amount of poor solvent is injected under ultrasonic conditions, causing the solubility of the luminescent molecules to decrease rapidly and aggregate, thereby precipitating in the form of small particles, and then the remaining organic solvent is removed to obtain luminescent molecule nanoparticles. The nano-coprecipitation method is preferred because it is easy to operate and the nanoparticles produced are small and uniform in size.
[0048] In the nano-coprecipitation method, the luminescent molecular nanoparticles can be surface-functionalized using amphiphilic polymers. In the manufacturing process, the luminescent molecules and the amphiphilic polymers self-assemble, and one end of the amphiphilic polymer has a hydrophobic functional group and the other end has a hydrophilic functional group, so that the luminescent molecular nanoparticles coated with the amphiphilic polymer can be obtained, and the functional groups (e.g., amino and carboxyl groups) of the amphiphilic polymer are exposed on the outer surface of the nanoparticles, thereby obtaining surface-functionalized luminescent nanoparticles. Functional groups such as nucleic acids, polypeptides, sugars, proteins, or antibodies can react with the functional groups exposed on the outer surface of the nanoparticles of the amphiphilic polymers through condensation reaction or bioorthogonal click reaction, to obtain luminescent molecular nanoparticles with recognition function.
[0049] In the present invention, the amphiphilic polymer is also called a copolymer molecule. As the copolymer molecule, copolymer molecules commonly used in this field, such as polystyrene-polyacrylic acid block copolymer (PS-PAA), polystyrene maleic anhydride copolymer (PSMA) or poly(isobutylene-alt-maleic anhydride) (PIMA), etc., as shown in the following chemical formula 9, can be used, but are not limited thereto.
[0050] [ka]
[0051] The diameter of the nanoparticles obtained by the nanocoprecipitation method can reach a minimum of 1 nm to 2 nm.
[0052] The surface functionalization of hot exciton nanoparticles is not limited to the above-mentioned modification method using amphiphilic polymers, and other modification methods such as direct functionalization (i.e., directly modifying luminescent molecules with functional groups such as alkoxy chains, amino / carboxyl groups, or biomolecules having targeting functions by a covalent bonding method) and physical coating (i.e., coating nanoparticles with phospholipids or silicon dioxide, etc.) can also be adopted.
[0053] By surface functionalizing the luminescent molecular nanoparticles, a large number of functional groups can be provided on the surface of each nanoparticle, and a large number of oligonucleotides can be attached to the nanoparticle, thereby amplifying the electrochemical signal and improving the sensitivity of ECL detection.
[0054] (Modification of hot exciton nanoparticles) In the present invention, the modification of hot exciton nanoparticles refers to the modification of hot exciton nanoparticles with oligonucleotides. Specifically, the above-mentioned surface-functionalized hot exciton nanoparticles are modified with an oligonucleotide chain modified with a quencher molecule to obtain oligonucleotide-modified hot exciton nanoparticles (hereinafter, sometimes referred to as "ECL nanoprobes").
[0055] The binding method between the oligonucleotides and the hot exciton nanoparticles is a covalent bond reaction (e.g., NH 2 The bonding method is not limited to cross-linking by --COOH), but may be other bonding methods such as electrostatic action or affinity adsorption.
[0056] The oligonucleotide chain used for modification may be a double-stranded oligonucleotide chain (e.g., dsDNA, etc.) or a single-stranded oligonucleotide chain (e.g., RNA, ssDNA), etc., and specifically, can be appropriately selected depending on the type of Cas enzyme used.
[0057] In addition, since the solidarity cleavage activity of the Cas enzyme is non-specific, the nucleotide sequence constituting the oligonucleotide chain is not particularly limited and may be any sequence. The length of the oligonucleotide chain is also not particularly limited, and may be designed with reference to various oligonucleotide chains for linking that are often used in the prior art, as long as the quencher molecule can be bound to the hot exciton nanoparticle and resonance energy transfer can occur between the quencher molecule and the hot exciton nanoparticle.
[0058] From the viewpoint of sensitivity to cleavage by Cas enzyme, the number of nucleotides in the oligonucleotide strand should not be too large, and as a single strand, it is preferably 3 to 20, more preferably 4 to 11, and even more preferably 5, 6, 7, 8, 9, 10, 11 or 12.
[0059] The oligonucleotide chain of the present invention is modified with a quencher molecule. The dynamic quenching of the quencher molecule occurs by fluorescence resonance energy transfer (FRET) or collisional quenching. Since the light absorption of the quencher molecule overlaps with the fluorescence emission of the hot exciton nanoparticle, the resonance energy can be transferred from the excited nanoparticle to the quencher molecule, and the emission of the hot exciton organic light-emitting molecule can be quenched.
[0060] The quencher molecule may be a quencher molecule having a resonance energy transfer characteristic commonly used in the art, and is not particularly limited. For example, a black hole quencher may be used. TM Reagents, i.e. BHQ-based quenchers, dark quenchers (e.g. DABCYL series quenchers, etc.), BlackBerry TM Quenchers (i.e., BBQ series quenchers), Blueberry quenchers (i.e., BLU series quenchers), or amine-reactive quenchers (QSY series quenchers) can be used. Among them, BHQ quenchers are often used. All of these quenchers are commercially available (e.g., LGC, BiochTechnologies, Inc., 2006). TM ) etc.) can be obtained.
[0061] The method for connecting the quencher molecule to the oligonucleotide is not particularly limited, and any method commonly used in the art can be used. The quencher molecule may be connected to the end of the oligonucleotide or may be inserted into the oligonucleotide sequence.
[0062] 1 is a schematic diagram showing a method for producing an electrochemiluminescent nanoprobe of the present invention. Taking the hot exciton organic light-emitting molecule BCzP-BT molecule produced in Example 1 of the present invention as an example, the hot exciton organic light-emitting molecule BCzP-BT molecule is polymerized with the copolymer molecule PSMA by nano-coprecipitation to obtain hot exciton nanoparticles (BB NRs), and then an oligonucleotide DNA with a quencher molecule BHQ connected to its end is polymerized with NH 2 The hot exciton nanoparticles are connected by a covalent reaction of --COOH, thereby obtaining the electrochemiluminescence nanoprobe (ECL nanoprobe) of the present invention.
[0063] In the present invention, the oligonucleotide modified with the quencher molecule functions as the signal switch of the present invention together with the Cas enzyme described below. Specifically, when the oligonucleotide is not cleaved by the activated Cas enzyme, the quencher molecule is connected to the surface of the hot exciton nanoparticle via the oligonucleotide and exerts a quenching effect on the hot exciton organic luminescent molecule, and the sensor electrode displays a low ECL intensity (ECL OFF). On the other hand, when the oligonucleotide is cleaved by the activated Cas enzyme, the quencher molecule is detached from the surface of the hot exciton nanoparticle, and the sensor electrode displays a strong ECL signal (ECL ON).
[0064] <Electrochemiluminescence sensor> The electrochemiluminescence sensor (hereinafter sometimes referred to as "ECL sensor") of the present invention can be obtained by dropping the above-mentioned ECL nanoprobe onto a working electrode.
[0065] The working electrode used in the present invention is not particularly limited, and may be one of electrodes commonly used in ECL detection, such as a glass carbon electrode (GCE), an indium tin oxide (ITO) electrode, or a screen-printed electrode (SPE). An indium tin oxide electrode is preferably used, and a three-electrode system is more preferably used. The electrode system includes, for example, a platinum wire counter electrode, an Ag / AgCl reference electrode, and an indium tin oxide (ITO) working electrode.
[0066] In addition, as verified in the examples of the present invention later, gold has a good catalytic effect on the co-reactant tripropylamine, etc., and therefore, compared with an ITO electrode, a gold-indium tin oxide (Au-ITO) electrode can further enhance the ECL signal, so that it is more preferable to use an Au-ITO electrode in the present invention.
[0067] <Electrochemiluminescence detection method> The electrochemiluminescence detection method of the present invention (hereinafter, sometimes referred to as "ECL detection method") uses the above-mentioned ECL sensor. The ECL detection method of the present invention may further include an enzyme reaction step of adding a sample to be measured to a Cas enzyme catalyst system containing a guide nucleic acid capable of binding to a target nucleic acid to obtain a sample reaction solution, and a sample detection step of adding the sample reaction solution to the electrochemiluminescence sensor, collecting and analyzing an electrochemiluminescence signal.
[0068] In the ECL detection method of the present invention, the ECL sensor of the present invention may be manufactured at the time of use, rather than being used as is. In this case, the ECL detection method of the present invention may further include a hot exciton chip manufacturing step of dropping the ECL nanoprobe of the present invention onto the working electrode to obtain the hot exciton chip of the present invention (i.e., the ECL sensor).
[0069] The ECL detection method of the present invention can detect a target molecule in a sample to be measured. The sample to be measured is not particularly limited, and may be, for example, urine, blood, serum, cerebrospinal fluid, saliva, etc. The target molecule is not particularly limited, and may be, for example, a nucleic acid, a protein, a small chemical molecule, etc.
[0070] In the present invention, an enzyme-catalyzed reaction or other specific chemical reaction is used as the target recognition and signal conversion unit. When a target molecule is dropped, the signal switch state of the ECL nanoprobe can be changed by the enzyme reaction or chemical reaction, thereby realizing qualitative or quantitative detection of the target signal.
[0071] As the enzyme used in the enzymatic catalytic reaction, for example, a Cas enzyme having collateral cleavage activity among CRISPR / Cas enzymes can be used, the above activity belonging to the cleavage activity of non-specific nucleases, and when the Cas enzyme is targeted to a target nucleic acid molecule, the Cas enzyme is activated and acquires the non-specific activity of cleaving any nucleic acid molecule.
[0072] The Cas enzyme may include at least one Cas protein selected from, for example, Cas12 (VA type), Cas13 (VI type) and Cas14 (VF type), for example, at least one Cas protein selected from Cas12a, Cas12b, Cas13a, Cas13b, Cas14a, Cas14b and Cas14c. Here, Cas12 targets dsDNA (double-stranded DNA), Cas13 targets ssRNA (single-stranded RNA), and Cas14 targets ssDNA. In addition, Cas12a further has non-specific cleavage activity (also called trans-cleavage activity) against ssDNA, and therefore can further target ssDNA.
[0073] Additionally, Cas12 enzyme is more preferred because it targets DNA, is commercially mature, and can be used in other non-nucleic acid detection areas in addition to DNA (e.g., proteins, small biological molecules, etc.).
[0074] In the present invention, any nucleic acid sequence can be targeted by designing and synthesizing a guide RNA (gRNA) for the Cas enzyme. The gRNA consists of two parts, one is CRISPR RNA (crRNA), which is a 17-20 base long nucleotide sequence that complementarily pairs with the target nucleic acid; and the other is tracr RNA, which acts as a scaffold to help the Cas enzyme fold. The guide RNA activates the Cas enzyme by binding to the oligonucleotide of the target nucleic acid. The activated Cas enzyme cleaves the oligonucleotide connected to the ECL nanoprobe by its solidarity cleavage activity, changing the signal switch state of the ECL nanoprobe.
[0075] Hereinafter, the principle of the signal switch of the present invention and the manufacturing and detection method of the ECL detection chip of the present invention will be specifically described using the hot excitonic organic nanorods (BB NRs) and the sensor array prepared in the embodiment of the present invention as examples.
[0076] The principle of the signal switch of the present invention will be specifically described using the ECL detection chip shown in FIG. 2 as an example. FIG. 2 is a schematic diagram of an ECL switch based on the ssDNA-BB NRs nanoprobe of the present invention. The hot exciton nanoparticles (BB NRs) of the present invention are connected to an oligonucleotide (ssDNA) modified with a quencher molecule (BHQ) at the end to obtain the ECL nanoprobe of the present invention (ssDNA-BB NRs nanoprobe), which is used as a reporter probe in ECL detection. Since the end of the ssDNA is modified with BHQ, the BB NRs is in the ECL OFF state. The ssDNA-BB NRs nanoprobe is directly dropped onto the surface of the ITO electrode to construct an ECL sensor interface. When the reaction solution is dropped onto the sensor interface and the Cas enzyme (Cas12a enzyme) is not activated, the BHQ is connected to the BB NRs surface via the ssDNA, and the sensor electrode displays low ECL intensity (ECL OFF). Conversely, when the target molecule is present and the Cas12a enzyme is activated, the ssDNA is cleaved, thereby releasing the BHQ from the BB NRs surface, restoring the ECL of the BB NRs and generating a strong ECL signal at the sensor interface (ECL ON).
[0077] The manufacturing and detection method of the ECL detection chip of the present invention will be specifically described with the ECL detection method shown in FIG. 3 as an example. FIG. 3 is a schematic diagram of the manufacturing and detection of a sensor array based on ssDNA-BB NRs of the present invention. First, the ECL nanoprobe of the present invention is dropped onto an indium tin oxide (ITO) electrode or a gold-indium tin oxide (Au / ITO) electrode obtained by deposition of gold or the like, to obtain an ECL electrode (i.e., an ECL sensor) of the present invention. A reaction solution containing Cas protein, crRNA, and a target nucleic acid to be measured that may be contained therein is dropped onto the ECL electrode, and when the target molecule is not present and the Cas enzyme is not activated by the above-mentioned signal switch, the sensor electrode displays low ECL intensity (ECL OFF). On the other hand, when the target molecule is present and the Cas12a enzyme is activated, the ECL of the BB NRs is restored, generating a strong ECL signal (ECL ON) at the sensor interface, thereby realizing electrochemiluminescence detection based on the hot exciton organic luminescent molecule of the present invention.
[0078] From the viewpoint of obtaining a higher ECL signal intensity, it is preferable to optimize the ECL detection conditions, such as the concentration of the Cas protein in the sample reaction solution, the ratio of the Cas protein and the crRNA used, and the reaction time of the sample reaction solution on the chip (e.g., the incubation time).
[0079] The concentration of the Cas protein is not particularly limited, but from the viewpoint of obtaining a higher ECL signal intensity, it may be, for example, 40 nM or more, preferably 42 nM or more, more preferably 45 nM to 70 nM, and particularly preferably 50 nM to 60 nM.
[0080] The ratio of the Cas protein to the crRNA is not particularly limited, but from the viewpoint of obtaining a higher ECL signal intensity, it is preferable that the amount of the crRNA is greater than that of the Cas protein. For example, the ratio of the Cas protein to the crRNA may be 1:1.25 to 1:5, preferably 1:1.35 to 1:4, more preferably 1:1.5 to 1:3, and particularly preferably 1:1.5 to 1:2.
[0081] The incubation time of the sample reaction solution on the chip is not particularly limited, but from the viewpoint of obtaining a higher ECL signal intensity, it may be, for example, 30 minutes or more, preferably 35 to 120 minutes, more preferably 37 to 90 minutes or more, and particularly preferably 40 to 60 minutes.
[0082] As verified by the examples described later in the present invention, the ECL efficiency of the hot exciton material of the present invention reaches 56.7%, and the fluorescence quantum yield (Φ PL) can reach more than 89%, which is higher than the previously reported Pdots based on the thermally activated delayed fluorescence (TADF) principle (the highest reported organic ECL nanomaterial efficiency) (Anal. Chem. 2022, 94, 15695-15702) and Pdots based on conventional fluorescent materials (Chem. Sci. 2019, 10, 6815; Anal. Chem. 2016, 88, 845).
[0083] Figure 4 is a schematic diagram showing the light emission principle of TADF compounds and hot exciton materials. As shown in Figure 4, the RISC process of TADF compounds is 1 and S. 1 Because the lowest singlet state (S 1 ) and the triplet (T 1 ) excited states and the charge transfer (CT) nature of both states results in a low Φ PL In addition, the T 1 From S 1 The slow reverse intersystem crossing (RISC) to triplet excitons is likely to cause the accumulation of long-lived triplet excitons leading to their severe quenching. Contrary to the cold exciton pathway in TADF compounds, the RISC in hot exciton materials is more likely to occur at higher energy levels (hRISC,T m →S n ,m≧2,n≧1). Here, large T m -T 1 The energy gap is T m From T 1 Suppresses internal conversion (IC) to narrow T m -S n Energy splitting promotes hRISC. Thus, with accelerated RISC, hot exciton materials utilize triplet excitons better than TADF materials. The hRISC process is T 1 Also, unlike the strong CT characteristics of TADF materials, hot exciton materials have HLCT excited state properties, where S 1 The condition is LE or LE-dominant HLCT condition, and T m and S n Since the state is a CT state, it has a high ΦPL and achieve 100% exciton utilization efficiency.
[0084] Also, taking the detection of HPV16 DNA as an example, the ECL detection method of the present invention is compared with other methods described in the prior art in terms of detection range and detection limit, and the comparison results are shown in Table 1.
[0085]
Table 1
[0086] Note that the superscript characters 1 to 6 indicate the following documents respectively. 1: L. Wang et al., Microchem. J. 2022, 181, 107818. 2: Y. Nie et al., Biosens. Bioelectron. 2020, 160, 112217. 3: P. Liu et al., Biosens. Bioelectron. 2021, 176, 112954. 4: Y. He et al., ACS Appl. Mater. Interfaces, 2021, 13, 298. 5: S. Jampasa et al., Sensor. Actuat. B-Chem, 2018, 265, 514. 6: Y. He et al., Sensor. Actuat. B-Chem, 2020, 320, 128407.
[0087] As can be seen from Table 1, the ECL chip (sensor) manufactured based on the hot exciton organic light-emitting molecule of the present invention has a wider detection range and higher sensitivity than other reported ECL chips.
[0088] <ECL Detection Kit> The ECL detection kit of the present invention may directly contain the ECL sensor of the present invention, or may contain the ECL nanoprobe of the present invention, which is dropped onto the working electrode during detection. In addition to the ECL sensor, the kit may contain other reagents necessary for ECL detection, such as a detection reagent containing a Cas enzyme or an instruction manual.
[0089] Although the electrochemiluminescent nanoprobe and its manufacturing method and applications of the present invention have been described above based on the embodiments, the present invention is not limited thereto. As long as it does not deviate from the spirit of the present invention, the scope of the present invention also includes forms obtained by applying various modifications to the embodiments that a person skilled in the art can conceive, and other forms constructed by combining some of the components in the embodiments. EXAMPLES
[0090] The hot exciton nanoparticles, ECL nanoprobes, ECL detection methods, etc. of the present invention will be specifically described below with reference to examples, although the present invention is not limited to these examples.
[0091] The reagents, experimental methods and devices used in the examples are as follows. (1) Reagents: Tetrakis(triphenylphosphine)palladium (Pd(Pph 3 ) 4 ) is purchased from Bide Pharmaceutical Technology Co., Ltd. (Shanghai, China). 4-(9H-carbazol-9-yl)phenylboronic acid pinacol ester is purchased from Macklin Biochemical Technology Co., Ltd. (Shanghai, China). 4,7-Dibromobenzo[c]-1,2,5-thiadiazole is purchased from Aladdin Biotech Co., Ltd. (Shanghai, China). EnGen® Lba Cas12a (10 μM solution) is purchased from New England Biolabs (Ipswich, MA, UK). Polystyrene-maleic anhydride (PSMA, average Mw: 1700), 4-(2-hydroxyethyl)-1-piperazineethanesulfonic acid (HEPES), polyethylene glycol (PEG, average Mw: 3350), 1-(3-(dimethylamino)propyl)-3-ethylcarbodiimide hydrochloride (EDC) and tetrabutylammonium chloride are all purchased from Sigma-Aldrich Co., Ltd. (Shanghai, China). Tripropylamine (TPrA, >98%) is purchased from J&K Chemical Ltd. (Beijing, China). Indium tin oxide (ITO) glass sheets (100 × 100 mm × 1.1 mm) are purchased from Zhuhai Kaivo Optoelectronic Technology Co., Ltd. (Zhuhai, China). Diethyl carbonate (DEPC) water and all oligonucleotides listed in Table 2 are both purchased from Sangon Bioengineering Co. Ltd. (Shanghai, China). Phosphate buffer (PBS, 0.1M, pH 7.4) is a KH 2 PO 4 and Na 2 HPO 4 It is prepared by mixing stock solutions of:
[0092] The oligonucleotide sequences used in the examples are as follows:
[0093] [Table 2]
[0094] (2) Experimental method and equipment TEM is obtained with a TECNAIG2F 20 transmission electron microscope (FEI, USA). Zeta potentials are recorded using a 90 Plus DynaPro NanoStar (Brookhaven Instrument Corporation, USA). 1 H NMR spectra were recorded on a Bruker AvanceIII 500HD spectrometer (Germany) using deuterated CDCl 3 The measurement is performed using tetramethylsilane (TMS) as the internal standard. UV-vis absorption spectra are obtained by a UV-3600 spectrophotometer (Shimadzu, Japan). Photoluminescence (PL) spectra and fluorescence lifetimes were measured using an FLS-980 fluorescence spectrophotometer (Edinburgh, UK). AFM images were obtained using an atomic force microscope (BRUKER Dimension Icon, Germany) in ScanAsyst mode. Deposit a 5 nm Cr and a 50 nm Au layer onto the ITO glass sheet by a PVD 75 electron beam evaporation system (Kurt J. Lesker, USA). The ECL spectrum was obtained using a homemade ECL spectrometer in the laboratory of Professor Guizheng Zhou of Shandong University. The spectrometer was heated with liquid N 2 The system consisted of an Acton SP 2300i monochromator with a 3000MHz-cooled PyLoN 400BR-eXcelon digital CCD detector (Princeton, USA) and a VersaSTAT3 electrochemical analyzer (Princeton, USA). Cyclic voltammetry experiments are performed on a CHI 630D electrochemical workstation (CHI instruments Inc., China). Anodic and cathodic ECL experiments were carried out in a home-made reaction chamber of an MPI-EII ECL analyzer (Xi'an Remex, China), which employs a three-electrode system. ECL imaging is performed with a home-made ECL imaging system equipped with a focusing lens (EF 50mm f / 1.2L USM, Canon), an electron multiplying charge-coupled device (EMCCD, iXon Ultra, Andor, UK) and a CHI-660D electrochemical workstation, with a Au / ITO electrode as the working electrode, an Ag / AgCl wire as the reference electrode and a Pt wire as the counter electrode.
[0095] Example 1: Fabrication and characterization of hot excitonic organic nanorods (BB NRs)
[0096] a. Synthesis of hot exciton molecule BCzP-BT First, 4-(9H-carbazol-9-yl)phenylboronic acid pinacol ester (Cz, 1.1817 g, 3.2 mmol), 4,7-dibromobenzo[c]-1,2,5-thiadiazole (BT, 0.4145 g, 1.41 mmol), K 2 CO 3 (2.0040g, 14.5 mmol) and tetrakis(triphenylphosphine)palladium (Pd(Pph 3 ) 4 , 0.2311g, 0.2 mmol) was added to a Schlenk tube containing a mixture of 20 mL toluene and 4 mL water, and the Schlenk tube was then stirred under argon atmosphere at 90°C for 18 hours. The reacted mixture was then extracted with dichloromethane, and purified by silica gel column chromatography using petroleum ether and dichloromethane as eluents to obtain 0.7512g BCzP-BT product (i.e., 4,7-bis(4-(9H-carbazol-9-yl)phenyl)benzo[c][1,2,5]thiadiazole (p-BCzP-BT), hereinafter also abbreviated as "BCzP-BT"), with a yield of 86%. Nuclear magnetic ( 1 The synthesis of the BCzP-BT molecule was verified by H NMR and mass spectroscopy, and the results are shown in Figures 5A and 5B. Figures 5A and 5B show the nuclear magnetic resonance (H NMR) and mass spectroscopy of the BCzP-BT molecule produced in Example 1 of the present invention. 1 1 H NMR) and mass spectrometry results. Here, FIG. 5A shows the nuclear magnetic resonance (1 5A and 5B show the results of H NMR (NMR) analysis of the BCzP-BT molecule, and FIG. 5B shows the results of mass spectrometry of the BCzP-BT molecule.
[0097] FIG. 5A shows the nuclear magnetic resonance ( 1 5A and 5B show the results of H NMR analysis and mass spectrometry of the BCzP-BT molecule, respectively. As can be seen from Figures 5A and 5B, the present invention successfully synthesized the BCzP-BT molecule.
[0098] b. Fabrication of hot excitonic organic nanorods (BB NRs) First, 2.5 mL of a THF solution containing 50 μg / mL BCzP-BT and 10 μg / mL poly(styrene-maleic anhydride copolymer) (PSMA, Mn=1700) was sonicated at room temperature for 20 min. Then, the above solution was quickly injected into 10 mL of water and sonicated for 30 s. The solvent THF was removed by rotary evaporation at 35 °C, and further filtered with a polyethersulfone syringe to obtain BB NRs.
[0099] c.Excited states and characterization of BCzP-BT molecules The excited state of the BCzP-BT molecule prepared in Example 1 of the present invention was analyzed, and the results are shown in Figures 6A and 6B. Figures 6A and 6B are diagrams showing the excited state analysis results of the BCzP-BT molecule prepared in Example 1 of the present invention. Here, Figure 6A shows the normalized UV-Vis absorption and FL spectra of BCzP-BT in different polar solvents, and Figure 6B shows the normalized UV-Vis absorption and FL spectra of CzP, BT and BCzP-BT in the BCzP-BT molecule at 10 -5 The FL spectrum of M THF solution is shown.
[0100] First, we considered the normalized UV-Vis absorption and fluorescence (FL) spectra of the BCzP-BT molecule in solvents of different polarity. The results are shown in Figure 6A. Because the charge in the molecule is transferred from the Cz to the BT unit, BCzP-BT exhibits a broad absorption at about 400 nm, and the shape and position of the UV absorption peak did not change significantly with increasing solvent polarity. However, with increasing solvent polarity, the fluorescence spectrum of BCzP-BT exhibited a red shift of 68 nm and the fluorescence peak became broader, indicating that the BCzP-BT molecule has a solvent effect. As can be seen from Figure 6A, the BCzP-BT molecule has a strong charge transfer state (CT) feature.
[0101] Next, the 10% of CzP, BT, and BCzP-BT in the BCzP-BT molecule -5 The difference in the FL spectra in M THF solution was analyzed, and the results are shown in Figure 6B. As can be seen from Figure 6B, the emission of the BCzP-BT molecule comes from the charge transfer from Cz to BT, and not from the monomer itself.
[0102] 7A and 7B are diagrams showing the excited state properties of the BCzP-BT molecule prepared in Example 1 of the present invention. Here, FIG. 7A shows the Stokes displacement (v a -v f 7A shows a curve of change in PL attenuation of BCzP-BT in THF versus the orientation polarizability (Δf) of the solvent, and FIG. 7B shows a curve of transient PL decay of BCzP-BT in THF.
[0103] Furthermore, to investigate the excited state properties of BCzP-BT, the Stokes displacement (v a -v f ) and the solvent orientation polarizability (Δf) change curve, and S is calculated based on the slope of the curve. 1 The dipole moment of was calculated, and the results are shown in Figure 7A.
[0104] In Figure 7A, two cross-section fitting lines are observed, with the dipole moment of the low polarity solvent being small and the dipole moment of the high polarity solvent being large, which correspond to the locally excited state (LE) and the charge transfer excited state (CT), respectively. For the medium polarity solvent, the excited state simultaneously exhibits the properties of the LE state and the CT state.
[0105] The fluorescence lifetime of BCzP-BT was also analyzed. The results are shown in FIG. 7B. FIG. 7B shows the transient PL decay curve of BCzP-BT in THF. As can be seen from FIG. 7B, BCzP-BT showed a single-index decay of 6.72 ns with no delay. The results indicate that the S 1 We further prove that the excited state is a hybrid local-charge-transfer excited state (HLCT) and not a simple mixture of LE and CT states.
[0106] 8A and 8B are diagrams showing the results of an analysis of the possibility of hot exciton processes in BCzP-BT produced in Example 1 of the present invention, in which Fig. 8A is a diagram showing the energy level distribution of the BCzP-BT molecule, and Fig. 8B is a diagram showing the results of a natural transition orbital simulation of the BCzP-BT molecule.
[0107] To verify the possibility of hot exciton processes, we calculated the energy levels of the lowest singlet and triplet excited states of BCzP-BT using TD-m062x / 6-311g(d), and the results are shown in Figure 8A.
[0108] According to the results in Figure 8A, T 2 and T 1 The band gap between (1.09 eV) and T suppresses triplet internal conversion. 2 and S. 1 The narrow gap (0.13 eV) between the triplet excitons promotes reverse intersystem crossing, thereby reducing quenching due to triplet exciton accumulation and allowing the triplet excitons to be efficiently utilized by the hot exciton channel.
[0109] In addition, natural transition orbital (NTO) simulations were performed on the BCzP-BT molecule using Multiwfn software. The simulation results are shown in Figure 8B. According to the results of Figure 8B, T 1 is a feature of the localized excited state (LE), and S m and T n is characterized by a charge-transfer excited state (CT), and S 1 has the characteristic of having a hybrid local charge-transfer excited state (S 1 (This is because the electrons in the β-state are concentrated in the BT and adjacent benzene rings, and the holes are distributed throughout the skeleton.)
[0110] Characterization of d.BB NRs: The characteristics of the BB NRs produced in Example 1 of the present invention were analyzed. The results are shown in Figures 9A to 9E. Figures 9A to 9E are diagrams showing the analysis results of the characteristics of the BB NRs produced in Example 1 of the present invention. Here, Figure 9A is a TEM image, Figure 9B is an AFM image, and Figures 9C, 9D, and 9E are diagrams showing the ultraviolet and fluorescent spectra and fluorescent lifetimes of the BB NRs and BCzP-BT, respectively.
[0111] First, the morphology of the synthesized BB NRs was analyzed by TEM and AFM. The TEM and AFM images are shown in Figures 9A and B, respectively. According to the results in Figures 9A and B, the BB NRs have a rod-like morphology with a width of about 30 nm and a length of about 200 nm.
[0112] 9C, 9D, and 9E show the ultraviolet and fluorescence spectra and fluorescence lifetimes of BB NRs and BCzP-BT, respectively. As can be seen from FIG. 9C, the BB NRs solution is light green in sunlight and emits bright yellow-green light when irradiated with 365 nm ultraviolet light. As can be seen from FIG. 9D, compared with BCzP-BT, the ultraviolet absorption of BB NRs showed a slight red shift around 400 nm, which may be due to the fact that BB NRs lower the transition energy in the polar environment in water. As can be seen from FIG. 9D, both BCzP-BT and BB-NR showed similar FL emission at 554 nm. As can be seen from FIG. 9E, the FL lifetime of both was about 6.7 ns, and these results showed that BB-NR has the same photophysical properties as BCzP-BT.
[0113] ECL characteristics of e.BB NRs The ECL properties of the BB NRs prepared in Example 1 of the present invention were analyzed. First, we performed annihilation ECL experiments to examine the stability of the BB NRs radical intermediate. The specific conditions for the annihilation ECL experiments are as follows. Electrode material: BB NRs / GCE Electrolyte: 0.1M PBS pH 7.4, nitrogen gas aeration for 20 minutes ECL: Cyclic voltammetry method Annihilation state ECL: Pulse step method Maximum voltage: +1.5V Lowest potential: -2.0V Scanning speed: 0.1V / s PMT: High voltage 800V
[0114] The experimental results are shown in Figures 10A and 10B. Figures 10A and 10B are diagrams showing the analysis results of the ECL properties of the BB NRs prepared in Example 1 of the present invention. Here, Figure 10A shows the cyclic voltammetry (CV) curve and ECL curve of the BB NRs / GCE, where the curve a shows the result of first performing the anodic scan, and the curve b shows the result of first performing the cathodic scan. Figure 10B shows the annihilation state ECL curve of the BB NRs / GCE.
[0115] FIG. 10A shows the cyclic voltammetry (CV) and ECL curves of BB NRs / GCE. As shown in FIG. 2 In PBS saturated with , the cyclic voltammetry (CV) curve of the glass carbon electrode modified with BB NRs (BB NRs / GCE) showed an oxidation peak at +0.95 V (corresponding to the oxidation of Cz) and a reduction peak at -1.45 V (corresponding to the reduction of BT).
[0116] In addition, as can be seen from Figure 10A, the scanning direction has a large effect on ECL. When the anodic scanning was performed first (curve a), weak ECL emission appeared only at +1.05 V (from 0 to +1.5 V and further to -2.0 V), whereas when the cathodic scanning was performed first (curve b), strong ECL emission appeared at both +1.0 V and -2.0 V (from 0 to -2.0 V and further to +1.5 V). These results demonstrated that the reduction state of BB NRs was more stable.
[0117] At the same time, the annihilated state ECL of BB NRs was detected using the pulse step method. The results are shown in Figure 10B. In Figure 10B, the left graph shows -2.0 to +1.5 V, and the right graph shows +1.5 to -2.0 V. The results in Figure 10B show that the transient ECL emission of BB NRs was observed only at +1.50 V, regardless of whether the initial potential was negative or positive, proving that the reduced state of BB NRs has higher stability.
[0118] We further investigated the ECL of BB NRs in the presence of a coreactant, and the analytical results are shown in Figure 11.
[0119] First, the anodic ECL behavior of BB NRs was considered using tripropylamine (TPrA) as a coreactant.
[0120] The specific experimental conditions for the anodic ECL experiment are as follows. Electrode material: BB NRs / GCE Electrolyte: 0.1M PBS containing 10mM TPrA pH 7.4 Test method: Cyclic voltammetry method Maximum voltage: +1.5V Lowest potential: 0V Scanning speed: 0.1V / s ECL: PMT, high voltage 400V Also, S 2 O 8 2- The cathodic ECL behavior of BB NRs was investigated using as a coreactant. The specific experimental conditions for the cathodic ECL experiment are as follows: Electrode material: BB NRs / GCE Electrolyte: 100mM K 2 S 2 O 8 Contains 0.1 M PBS pH 7.4 Test method: Cyclic voltammetry method Highest voltage: 0V Lowest potential: -2.0V Scanning speed: 0.1V / s ECL: PMT, high voltage 400V
[0121] The analysis results are shown in Figures 11A to 11F. Figures 11A to 11F are the analysis results of ECL of the BB NRs prepared in Example 1 of the present invention in the presence of a co-reactant. Here, Figures 11A, 11B, and 11C respectively show the anodic ECL behavior and mechanism of the BB NRs when tripropylamine (TPrA) is used as a co-reactant, and the curves a and c in Figures 11A and 11B show TPrA itself, the curve b shows the absence of TPrA, and the curve c shows the coexistence with TPrA. Figures 11D, 11E, and 11F respectively show the K 2 S 2 O 8 The cathodic ECL behavior and mechanism of BB NRs with co-reactant are shown in Fig. 11D and Fig. 11E. Curve a in Fig. 11D corresponds to S 2 O 8 2- Therefore, curve b is S 2 O 8 2- None, curve c is S 2 O 82- This indicates that it coexists with
[0122] As can be seen from FIG. 11A, tripropylamine (TPrA) itself (curve a) exhibits an irreversible oxidation peak at +0.98 V, with an onset potential of +0.57 V. · The radical is TPrA ·+ (TPrA oxidation product) is generated after deprotonation. As can be seen from Figures 11A and 11B, in the absence of TPrA (curve b), the oxidation of BB NRs starts at around +0.70 V, and the cation radical BB NRs ·+ As can be seen from Figures 11A and 11B, when coexisting with TPrA (curve c), the BB NRs / GCE showed oxidation peaks of TPrA and BB NRs and strong ECL emission reaching a peak value at +1.07 V. This phenomenon was observed when TPrA· and BB NRs ·+ The excited singlet and triplet states BB NRs ( 1 BBNRs * and 3 BBNRs * ) is attributed to the radiative relaxation of the
[0123] As can be seen from Figs. 11D and 11E, S 2 O 8 2- Itself (curve a) is strongly oxidizing at -1.07 V. 4 ·- However, its ECL emission is low and negligible. As can be seen from FIG. 11D and FIG. 11E, K 2 S 2 O 8 In the absence of BB NRs (curve b), the BB NRs / GCE showed a clear reduction peak at -1.55 V, accompanied by weak ECL emission, indicating that the BB NRs were reduced to the BB NRs. ·- As can be seen from Figs. 11D and 11E, K 2 S 2 O 8In the presence of BB NRs (curve c), the BB NRs / GCE produced a clear reduction current with a peak potential of −1.40 V and was accompanied by strong ECL emission. ·- and SO 4 - By reaction with 1 BBNRs * and 3 BBNRs * We attribute this to the generation of radiation from the ion beam (see Figure 11F).
[0124] In addition, 10 mM TPrA · or 100 mM K 2 S 2 O 8 In the presence of 1 mM Ru(bpy) 3 2+ The ECL efficiency of the BB NRs was verified by recording the current-time curves and ECL spectra of the BB NRs using Ru(bpy) as a standard. The specific experimental conditions were the same as those of the anodic ECL experiment and cathodic ECL experiment described above. The results are shown in Figures 12A to 12D and Table 3. Figures 12A to 12D show the ECL efficiency of the BB NRs using Ru(bpy) 3 2+ 12A and 12B are diagrams showing the ECL efficiency of the BB NRs prepared in Example 1 of the present invention relative to Ru(bpy), where FIG. 12A and FIG. 12B are diagrams showing the ECL efficiency of the BB NRs and Ru(bpy), respectively. 3 2+ 12C and 12D show the anodic current-time curves and ECL spectra of the modified GCE. 3 2+ The cathodic current-time curves and ECL spectra of the modified GCE are shown.
[0125] Table 3 shows the results of BB NRs / GCE and Ru(bpy) 3 2+ The relative ECL efficiency with respect to / GCE is shown.
[0126] [Table 3]
[0127] In addition, φ ECL is calculated using the following formula (1).
[0128]
number
[0129] Here, φ and φ°, I and I°, Q and Q° respectively represent the ECL efficiency, the ECL intensity integral (integrated ECL spectrum vs. wavelength), and the consumed charge (integrated CV curve vs. time) of the sample and the standard.
[0130] As can be seen from Figures 12A to 12D and Table 3, the BB NRs of the present invention exhibit superior ECL efficiency to conventional fluorescence-based Pdots (Z. Wang et al., Adv. Funct. Mater. 2020,30,2000220; Y. Feng et al., Anal. Chem. 2016, 88, 845; Z. Wang et al., J. Phys. Chem. Lett. 2018,9,5296) and TADF Pdots (C. Wang et al., Anal. Chem. 2022,94,15695) in the presence of the same or even lower concentrations of co-reactant, due to the hot exciton mechanism that endows the BB NRs with high radiative transition rates and efficient exciton utilization efficiency.
[0131] Furthermore, the ECL assignment of BB NRs was considered. The analysis results are shown in Figures 13A to 13C. Figures 13A to 13C are diagrams showing the analysis results of the ECL assignment of BB NRs produced in Example 1 of the present invention. Here, Figure 13A is a diagram showing the anodic and cathodic ECL spectra and FL spectrum of BB NRs, and Figure 13B is a diagram showing the CV curve of a glass carbon electrode modified with BB NRs. Figure 13C is a schematic diagram showing the band gap between the lowest unoccupied molecular orbital (LUMO) and the highest occupied molecular orbital (HOMO) of the BCzP-BT molecule.
[0132] First, the anodic and cathodic ECL spectra and FL spectra of the BB NRs were tested. The test results are shown in Figure 13A. The specific test conditions for the anodic and cathodic ECL spectra were the same as those of the above anodic and cathodic ECL experiments.
[0133] Figure 13A shows the anodic and cathodic ECL spectra and FL spectra of BB NRs. As can be seen from Figure 13A, the emission peaks of the anodic and cathodic ECL of BB NRs matched well with its FL emission peaks, both at 560 nm, indicating that the ECL and FL processes of BB NRs have the same excited states. These excited states are generated by band gap transitions.
[0134] The CV curve of BB NRs in the organic phase was also examined, and the results are shown in Figure 13B.
[0135] Here, the specific test conditions for the organic phase CV are as follows. Electrode material: BB NRs / GCE Electrolyte: 0.1 M tetrabutylammonium chloride in tetrahydrofuran solution, nitrogen gas purged for 20 minutes Test method: Cyclic voltammetry method Maximum voltage: +1.5V Lowest potential: -2.2V Scanning speed: 0.1V / s
[0136] Figure 13B shows the CV curve of the glass carbon electrode modified with BB NRs, and Figure 13C shows the band gap between the lowest unoccupied molecular orbital (LUMO) and highest occupied molecular orbital (HOMO) of the BCzP-BT molecule. As can be seen from Figures 13B and 13C, the oxidation peak of BB NRs corresponds to the oxidation of two carbazoles, but since carbazoles are prone to electrochemically react to form dimers, the CV of BB NRs shows an irreversible oxidation wave, and its reduction peak is generated by the reduction of benzothiadiazole, and since benzothiadiazole has two electron-withdrawing imino bonds (C=N), its CV curve also shows two consecutive reduction peaks.
[0137] Example 2: ECL nanoprobes 1) Oligonucleotide modified BB NRs probe: a. Preparation of ssDNA-BB NRs First, 12 μL of polyethylene glycol (PEG, Mw=3350) and 12 μL of 1 M 4-(2-hydroxyethyl)-1-piperazineethanesulfonic acid (HEPES) were added to 600 μL of BB NRs in order, and then the pH of the solution was adjusted to 7.4 with 0.1 M NaOH. Then, 40 μL of single-stranded DNA modified with black hole quencher 2 (BHQ2) (ssDNA-BHQ2, 100 μM) and 24 μL of freshly prepared EDC (10 mg / mL) were added, and the mixture was stirred at room temperature in the dark for 24 hours, after which the free ssDNA-BHQ2 was centrifuged and removed by ultrafiltration to obtain ssDNA-BB NRs. The mixture was diluted to have the same absorbance at a wavelength of 410 nm as the BB NRs, and stored away from light.
[0138] b. Characterization of ssDNA-BB NRs The ultraviolet absorption spectrum and Zeta potential of the ssDNA-BB NRs were measured. The results are shown in Figures 14A to 14C. Figures 14A to 14C are diagrams showing the analysis results of the characteristics of the ssDNA-BB NRs probe produced in Example 2 of the present invention. Here, Figure 14A is a diagram showing the ultraviolet absorption spectrum and FL spectrum of the ssDNA-BB NRs probe. Curves a, b, c, and d in the figure respectively show the ultraviolet absorption spectra of ssDNA-BB NRs, ssDNA, and BB NRs, and the FL spectrum of BB NRs. Figure 14B is a diagram showing the analysis results of the Zeta potential. Figure 14C is a diagram showing the ultraviolet analysis results of the ultrafiltered liquid at each time in the manufacturing process of the ssDNA-BB NRs probe. The numbers 1 to 9 in the figure indicate the filtrates from the first to ninth times, in order.
[0139] As can be seen from curve a in Figure 14A, the UV-vis absorption of ssDNA-BB NRs not only has the absorption peak of BB NRs at 410 nm, but also has the absorption peak of ssDNA at 260 nm and the absorption peak of BHQ2 at 580 nm. Also, as can be seen from Figure 14A, the broadband absorption band of BHQ2 overlaps with the FL emission peak of BB NRs (curve d), indicating that BHQ2 can quench the emission of BB NRs.
[0140] As can be seen from Figure 14B, the Zeta potential of ssDNA-BB NRs was determined, and compared to BB NRs, ssDNA-BB NRs had a more negative Zeta potential. These results demonstrated that the preparation of ssDNA-BB NRs probes was successful.
[0141] In addition, when ssDNABB NRs was purified by ultrafiltration, the filtrate was collected and its UV was measured. As can be seen from Figure 14C, with the increase in the number of ultrafiltrations, the absorption peaks of DNA and BHQ2 in the solution gradually decreased, which indicated that there was almost no free ssDNA-BHQ2 in the prepared ssDNA-BB NRs probe solution.
[0142] 2) ECL switch based on ssDNA-BB NRs nanoprobe a. Signal switch principle The ssDNA-BB NRs nanoprobe is explained as a reporter probe. As shown in Figure 2, the BB NRs is in the ECL OFF state because the end of the ssDNA is modified with BHQ. The ssDNA-BB NRs nanoprobe was directly dropped onto the surface of the ITO electrode to construct an ECL sensor interface. When the reaction solution is dropped onto the sensor interface and the Cas12a enzyme is not activated, the BHQ is connected to the BB NRs surface via the ssDNA, and the sensor electrode displays low ECL intensity (ECL OFF). On the other hand, when the target molecule (target nucleic acid) is present and the Cas12a enzyme is activated, the ssDNA is cleaved, which causes the BHQ to detach from the BB NRs surface, restoring the ECL of the BB NRs and generating a strong ECL signal at the sensor interface (ECL ON).
[0143] b. Signal switch verification First, we analyzed the switching response of Cas12a enzyme to ssDNA-BB NRs nanoprobes by fluorescence.
[0144] The test conditions for the Cas enzyme-fluorescence test are as follows: Detection device: Fluorescence excitation detection device Excitation wavelength: 365 nm Emission wavelength range: 400~700 nm PMT: 800V Before reaction: 50 μL of ssDNA-BB NRs + 50 μL of water After reaction: 50 μL of ssDNA-BB NRs + 50 μL Cas12a system In addition, Cas12a system: 2.5μL Cas12a (1μM) + 5μL crRNA (1μM) + 5μL NE buffer (10×) + 32.5μL DEPC water + 5μL HPV16 dsDNA (500 nM)
[0145] The results of the fluorescence test are shown in Figure 15A and Figure 15B. Figure 15A and Figure 15B are diagrams showing the analysis results of the feasibility of the ssDNA-BB NRs probe signal switch prepared in Example 2 of the present invention. Here, Figure 15A shows the fluorescence analysis results before (curve a) and after (curve b) the reaction of ssDNA-BB NRs and Cas12a system. Figure 15B shows the analysis results of the normalized ECL imaging intensity of different ITO electrodes. Here, curve a shows the BB NRs modified electrode, curve b shows the ssDNA-BB NRs modified electrode, curve c shows the result of adding 1 nM target molecule to the ssDNA-BB NRs+Cas12a+crRNA system modified electrode, and curve d shows the result of adding no target molecule to the ssDNA-BB NRs+Cas12a+crRNA modified electrode.
[0146] Figure 15A shows the fluorescence analysis results of the ssDNA-BB NRs and Cas12a system before (curve a) and after (curve b) the reaction. As shown in Figure 15A, after activating the Cas12a enzyme with 1 nM of the target molecule, the fluorescence of the ssDNA BB NRs was greatly restored (curve b).
[0147] Figure 15B shows the analysis results of normalized ECL imaging intensity of different ITO electrodes. As shown in Figure 15B, compared with the sensor electrode modified with BB NRs (curve a), there was almost no ECL imaging signal (curve b) at the sensor interface modified with ssDNA-BB NRs, indicating that the sensor interface was in the ECL OFF state. After adding 1 nM target molecule, the Cas12a enzyme was activated and cleaved the BHQ-ssDNA on the BB NRs, generating an ECL ON response, and the ECL intensity of the sensor electrode was restored to ~75% (curve c). This result demonstrated the feasibility of the ECL switch system based on the ssDNA-BB NRs nanoprobe.
[0148] Moreover, as can be seen from Figure 15B, the conjugation of DNA-BHQ2 with BB NRs resulted in 95.6% quenching of the ECL emission of BB NRs (curves a, b).
[0149] Example 3: Electrochemiluminescence detection method for HPV gene based on CRISPR / Cas12a conversion catalyst ECL imaging detection of sensor arrays constructed based on ssDNA-BB NRs
[0150] A. Detection design The detection method is constructed based on the “ECL switch of ssDNA-BB NRs nanoprobe” (Figure 2) and is used to detect HPV genes.
[0151] b. Manufacturing the detection chip and detection using the same: The specific detection flow is as shown in FIG.
[0152] The specific operation steps are as follows:
[0153] Step 1: Indium tin oxide (ITO) glass was ultrasonically cleaned with toluene, acetone, ethanol and ultrapure water for 5 min each, and then plated with a 5 nm thick chromium layer and a 50 nm thick gold layer by electron beam evaporation sputtering equipment to obtain Au / ITO electrodes.
[0154] Step 2: A porous seal (2 mm diameter, 1 mm depth, 4 × 7 well array) was attached to the surface of the Au / ITO electrode.
[0155] Step 3: 3 μL of ssDNA-BB NRs was dropped into each well, dried at 37 °C for 30 min, and then each well was carefully washed with diethylpyrocarbonate (DEPC) water.
[0156] Step 4: 0.15 μL LbCas12a (1 μM), 0.3 μL crRNA (750 nM), 0.3 μL NE Buffer (10×) and 1.95 μL DEPC water were reacted at 37°C for 10 minutes, after which 0.3 μL of different concentrations of HPV16 dsDNA or samples were added, and the resulting mixture was quickly dropped into the wells one by one and incubated at 37°C for 40 minutes.
[0157] Step 5: Each well on the chip was washed with DEPC water three times to remove the released BHQ2, and then dried at 37°C for 5 minutes, and then used for ECL imaging detection.
[0158] Step 6: ECL imaging detection was performed in a dark box with the Au / ITO electrode as the working electrode, the Ag / AgCL electrode as the reference electrode, the platinum wire electrode as the counter electrode, an electron-multiplying charge-coupled device (EMCCD, iXon Ultra, Andor, UK) as the signal readout device, and a 0.1 M pH 7.4 phosphate buffer solution of 5 mM tri-n-propylamine (TPrA) as the electrolyte. Cyclic voltammetry scanning was performed between 0 and +1.0 V with a scan rate of 0.1 V / s and an exposure time of 20 s.
[0159] c. Optimization of ECL detection conditions First, ECL detection of the present invention was performed under different detection conditions. The detection results are shown in Figures 16A to 16C. Figures 16A to 16C are diagrams showing the detection results of ECL detection under different detection conditions in Example 3 of the present invention. Here, Figure 16A shows the detection results at different Cas12a concentrations. Figure 16B shows the detection results at different ratios of Cas12a and crRNA used. Figure 16C shows the detection results at different incubation times on the chip.
[0160] Specifically, ECL detection was performed under different Cas12a concentrations, Cas12a and crRNA usage ratios, and reaction times on the chip as shown in Figures 16A to 16C, and ECL imaging measurements were performed using an electrolyte for the chips under different reaction conditions.
[0161] Note that Figure 16A shows the detection results at different Cas12a concentrations, Figure 16B shows the detection results at different Cas12a and crRNA usage ratios, and Figure 16C shows the detection results at different incubation times on the chip.
[0162] In the detection, the conditions when the ECL signal reaches the maximum platform period are selected as the optimal detection conditions. As shown in Figures 16A-16C, the optimal conditions for ECL detection in the present invention are Cas12a concentration of 50 nM, Cas12a:crRNA of 1:1.5, and incubation time of 40 min, respectively.
[0163] Next, the ECL images of the ITO and Au / ITO electrodes modified with BB NR in 0.1M, pH 7.4 PBS containing 5 mM TPrA were compared using ImageJ software. The results are shown in Figures 17A to 17C. Figures 17A to 17C are diagrams showing the ECL imaging results when the ITO electrode and Au / ITO of Example 3 of the present invention are used. Here, Figures 17A, 17B, and 17C show the CV, ECL curves, and ECL images of the ITO and Au / ITO electrodes modified with BB NR, respectively.
[0164] 17A-17C, compared with ITO modified with BB NRs, Au / ITO modified with BB NRs exhibits enhanced oxidation current, shifted oxidation peak to 0.93 V, 46-fold stronger ECL response, and improved ECL imaging quality. We attribute the difference to the better catalytic ability of gold for the oxidation of TPrA.
[0165] d.Detection performance Figures 18A and 18B are diagrams showing the detection results of ECL detection of HPV16 DNA target nucleic acid by a sensor array in Example 3 of the present invention. Here, Figure 18A shows the ECL imaging results and linear curves obtained by detecting HPV16 DNA at concentrations of 1 fM to 10 nM, and Figure 18B shows the analysis results of detection specificity of ECL detection of HPV16 DNA. Here, a shows 1 nM HPV18 DNA, b shows 1 nM HPV31 DNA, c shows 1 nM HPV58 DNA, d shows 100 pM HPV16 DNA, and e shows a mixture containing 1 nM HPV18, 31, 58 DNA and 100 pM HPV16 DNA.
[0166] Detection linearity and sensitivity: Under optimal detection conditions, ECL imaging detection was performed on HPV16 DNA target molecules with the constructed sensor array. The results are shown in Figure 18A. The upper part of Figure 18A shows the results of imaging detection for HPV16 DNA with concentrations from 1 fM to 10 nM. The results show that the ECL intensity increases with increasing HPV16 DNA concentration. The analog-to-digital conversion value (A / D count) of the ECL intensity and the logarithm of the HPV16 DNA concentration were plotted, and it was found that a good linear relationship was exhibited within the range of 1 fM to 10 nM. By calculating based on 3S / N, the detection limit of this method for HPV16 DNA is 0.6 fM.
[0167] Test for detection selectivity: In this embodiment, the detection specificity for the target nucleic acid HPV16 DNA was further tested in the presence of 10 times higher concentration of interfering DNA. The experimental results are shown in Figure 18B. Figure 18B shows the detection results of ECL detection for 100 pM HPV16 DNA (d) with 1 nM HPV18 DNA, 1 nM HPV31 DNA, and 1 nM HPV58 DNA alone (a, b, c) or in coexistence (e). The results show that only the sample solution containing HPV16 DNA has obvious ECL signal, and the method has good selectivity for the detection of HPV16 DNA.
[0168] Industrial Applicability As can be seen from the above examples, the present invention uses BCzP-BT as an emitting molecule to fabricate hot excitonic organic nanorods (BB NRs) with sensitive annihilation ECL and strong coreactant ECL emission for the first time. PL and high exciton utilization efficiency due to the charge transition state, which has superior Φ to conventional fluorescent materials and thermally activated delayed fluorescent materials. ECL Furthermore, by using the ECL nanoprobe of the present invention and by identifying the target nucleic acid by the CRISPR / Cas enzyme system and switching the signal from off to on, rapid and high-throughput detection of HPV16 DNA with simplified operation procedures was realized. Therefore, the present invention can establish a highly sensitive ECL detection platform for detecting HPV16 DNA. The detection effect is higher than that of Ru(bpy), which is considered to be the ECL standard. 3 2+ Therefore, the ECL detection method of the present invention is a feasible and reliable ECL detection method.
Claims
1. a hot exciton nanoparticle synthesis step of polymerizing the hot exciton organic light-emitting molecules and the copolymer molecules to synthesize hot exciton nanoparticles; a hot exciton nanoparticle modification step of modifying the obtained hot exciton nanoparticles with an oligonucleotide chain having a quencher molecule modification to obtain modified hot exciton nanoparticles; The method for producing an electrochemiluminescent nanoprobe comprises:
2. The hot exciton organic light-emitting molecule includes a donor (D) structure selected from group (a) of the following chemical formula (1) and an acceptor (A) structure selected from group (b) of the following chemical formula (2): The method of claim 1 . [Formula 1] [chemical 2]
3. The donor (D) is carbazole, The acceptor (A) is benzothiadiazole. The method according to claim 2 .
4. The hot exciton organic light-emitting molecule is BCzP-BT represented by the following chemical formula (3): The method according to claim 3. [C3]
5. The copolymer molecule is one of polystyrene-polyacrylic acid block copolymer (PS-PAA), polystyrene maleic anhydride copolymer (PSMA), and poly(isobutylene-alt-maleic anhydride) (PIMA), as shown in the following chemical formula (4): The method of claim 1 . [C4]
6. The hot exciton organic light-emitting molecules and the copolymer molecules are subjected to nano-coprecipitation to synthesize hot exciton nanoparticles; The method according to claim 5 .
7. the hot exciton nanoparticle is one of a nanoball, a nanotube, a nanorod, and a nano-onion; The method of claim 1 .
8. the quencher molecule is one of a black hole quencher, a dark quencher, and an amine-reactive quencher; The method of claim 1 .
9. A hot exciton nanoparticle in which a hot exciton organic light-emitting molecule and a copolymer molecule are polymerized, and the hot exciton nanoparticle is modified with an oligonucleotide chain having a quencher molecule modification. Electrochemiluminescent nanoprobes.
10. The hot exciton nanoparticles are formed by polymerizing hot exciton organic luminescent molecules and copolymer molecules, and an electrochemiluminescent nanoprobe is dropped onto the working electrode, the hot exciton nanoparticles being modified with an oligonucleotide chain having a quencher molecule modification. Electrochemiluminescence sensor.
11. the working electrode is one of a glassy carbon electrode, an indium tin oxide electrode, and a screen printed electrode; The electrochemiluminescence sensor according to claim 10.
12. the working electrode is a gold-indium tin oxide electrode; The electrochemiluminescence sensor according to claim 11.
13. The electrochemiluminescence sensor is an electrochemiluminescence sensor having a working electrode on which an electrochemiluminescence nanoprobe is dropped, the hot exciton nanoparticle being a hot exciton nanoparticle in which a hot exciton organic luminescent molecule and a copolymer molecule are polymerized, and the hot exciton nanoparticle is modified with an oligonucleotide chain having a quencher molecule modification. Electrochemiluminescence detection method.
14. an enzyme reaction step of adding a sample to be measured to a Cas enzyme catalyst system containing a guide nucleic acid capable of binding to a target nucleic acid to obtain a sample reaction solution; a sample detection step of adding the sample reaction solution to the electrochemiluminescence sensor and acquiring and analyzing an electrochemiluminescence signal; The electrochemiluminescence detection method of claim 13, further comprising:
15. In the sample reaction solution, the concentration of the Cas protein in the Cas enzyme is 40 nM or more; The electrochemiluminescence detection method according to claim 14.
16. The amount of crRNA used is greater than the amount of Cas protein used. The electrochemiluminescence detection method according to claim 14.
17. The incubation time of the sample reaction solution on the electrochemiluminescence sensor is 30 minutes or more. The electrochemiluminescence detection method according to claim 13.
18. An electrochemiluminescence sensor is an operating electrode on which an electrochemiluminescence nanoprobe is dropped, the hot exciton nanoparticle being a hot exciton nanoparticle in which a hot exciton organic luminescent molecule and a copolymer molecule are polymerized, the hot exciton nanoparticle being modified with an oligonucleotide chain having a quencher molecule modification; A detection reagent containing a Cas enzyme; A kit for electrochemiluminescence detection comprising:
Citation Information
Patent Citations
Fluorescent probes and application thereof to detection of neurotoxic agents
CN110981821A
Cited By
Computer program product and system
CN121833385A
